Reactivity and phase composition of Ca2SiO4 binders made by annealing of alpha-dicalcium silicate hydrate. (January 2015) - Link, T.; Bellmann, F.; Ludwig, H.M.; Ben Haha, M.
Abstract: This study investigates the production of highly reactive dicalcium silicate Ca2 SiO4 (C2 S). To that end, binders were synthesised by annealing of alpha-dicalcium silicate hydrate (α-C2 SH) between 400 and 800 °C. Two different heating sequences were tested. The phase compositions were determined by means of XRD. Depending on the annealing temperature and the heating conditions the cementitious materials consist of an X-ray-amorphous content as well as x-Ca2 SiO4 (x-C2 S) and γ-Ca2 SiO4 (γ-C2 S). The hydration kinetics of some selected binders were investigated by means of isothermal calorimetry. The specific reactivity of the phases produced by means of annealing was determined during the first 40 h of hydration by use of XRD and TGA. The resulting binders show the highest reactivity when low annealing temperatures (< 500 °C) were used. After 72 h, degrees of hydration of about 89% are achieved. The most reactive component is the X-ray-amorphous content, followed by x-C2 S.